A bismuth ferrite-based lead-free energy storage ceramic material and preparation method thereof

By introducing La3+, Mg2+ and Zr4+ ions into the bismuth-based ferrate BF-BT system, the oxygen vacancy is reduced, and the problem of large leakage current is solved, which significantly improves the energy storage density and efficiency of bismuth-based lead-free energy storage ceramic materials. .

CN116986892BActive Publication Date: 2024-12-20INNER MONGOLIA UNIV OF SCI & TECH
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202311067753.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-23
Publication Date
2024-12-20
Estimated Expiration
2043-08-23

AI Technical Summary

Technical Problem

There is a problem of large leakage current in the bismuth ferrate-based BF-BT system, which affects its energy storage performance, and existing research has not fundamentally solved this problem.

Method used

Introducing La3+, Mg2+ and Zr4+ ions, the oxygen vacancies are reduced, the material structure is optimized to improve energy storage density and efficiency.

Benefits of technology

The breakdown strength and energy storage density are significantly improved, the energy storage efficiency is improved, the electric field strength is increased from 60 kV/cm to 300 kV/cm, and the maximum energy storage density and efficiency is achieved when x=0.2.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116986892B_ABST
    Figure CN116986892B_ABST
Patent Text Reader

Abstract

The present invention discloses a bismuth ferrite-based lead-free energy storage ceramic material and a preparation method thereof. The bismuth ferrite-based lead-free energy storage ceramic material comprises a base ceramic having the following general chemical formula: (0.72-x)BiFeO3-0.28BaTiO3-xLa(Mg 1 / 2 Zr 1 / 2 )O3, wherein 0≤x≤0.24. The present invention introduces doping ions La, Mg and Zr to significantly reduce the oxygen vacancy concentration in the bismuth ferrite-barium titanate system, solves the problem of large leakage current, and improves the energy storage density and efficiency. The preparation method is simple and controllable, has high stability, uses green and environmentally friendly raw materials, and has low overall cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of ceramic materials, and in particular to a bismuth ferrite-based lead-free energy storage ceramic material and a preparation method thereof. Background Art

[0002] In the digital age, more and more smart digital products have emerged with the development of modern technology, bringing convenience to people's lives while increasing their proportion on the consumer side year by year. The gradual miniaturization and wearability of smart products have put forward new requirements for the upstream manufacturing industry. As my country's energy green and low-carbon transformation continues to advance, the proportion of new energy power generation continues to increase. Energy storage, as an indispensable part of new energy development, has received more and more attention, and the development of new green energy storage materials is imminent.

[0003] Dielectric energy storage materials based on electrostatic principles have been widely studied due to their high power density, high operating voltage, long cycle life and scalability. Among them, bismuth ferrite-based (BFO) relaxor ferroelectric ceramic materials have extremely high saturation polarization strength (~100 μC / cm 2 ), which has great advantages in energy storage applications. For single-phase BFO ceramics, there are disadvantages of large leakage current and low resistance, which are not conducive to its practical application. This is caused by the volatilization of Bi ions, the valence change of Fe ions and the existence of the second phase of impurities. Among them, the valence change of Fe ions during high-temperature sintering and the charge compensation that produces oxygen vacancies are the main factors causing the large leakage current. In order to solve this problem, the researchers synthesized BiFeO3-BaTiO3 (BF-BT) by synthetic solid solution to solve its existing defects, retaining its advantages to a large extent, and then through doping modification, its energy storage performance can be effectively improved. According to relevant reports, Wang et al. enhanced the breakdown electric field of the system by introducing Nd ions into BF-BT ceramics, but the energy storage density was only 1.82 J / cm 3 Liang et al. introduced Ba(Zn 1 / 2 Ta 2 / 3 )O3 increases cation disorder, reduces remanent polarization and coercive field, and Ta 5+ Ions compared to Fe 3+ The ions have a greater polarizability, which enables the ceramic material to maintain a high saturation polarization intensity while enhancing the relaxivity, and obtain 2.56 J / cm under an electric field of 160 kV / cm 3 Although these studies have improved the energy storage performance, they have not fundamentally solved the defects in the BF-BT system, and thus there are potential uncertainties. Therefore, how to solve the problem of large leakage current by reducing the oxygen vacancies in the material has become the key to the research. Summary of the invention

[0004] In view of the problem of large leakage current in the current BF-BT system, the present invention provides a bismuth ferrite-based lead-free energy storage ceramic material and a preparation method thereof. The ceramic material is prepared by introducing La 3+ Mg 2+ and Zr 4+ ions, reducing the oxygen vacancies in the structure, thereby obtaining higher energy storage density and energy storage efficiency.

[0005] In order to achieve the above-mentioned object, the present invention provides a bismuth ferrite-based lead-free energy storage ceramic material, which includes a base ceramic having the following chemical formula: (0.72-x)BiFeO3-0.28BaTiO3-xLa(Mg 1 / 2 Zr 1 / 2 )O3, where 0≤x≤0.24.

[0006] Preferably, the value range of x is 0.06≤x≤0.20.

[0007] Preferably, the value range of x is 0.12≤x≤0.18.

[0008] The present invention introduces La into the original BF-BT system. 3+ Mg 2+ and Zr 4+ Ion. La 3+ Radius and Bi 3+ Similarly, in BiFeO3, La 3+ Part of Bi 3+ Replacement, La 3+ -O 2- Compared with Bi 3+ -O 2- It has stronger stability, and the oxygen vacancies caused by the volatilization of bismuth oxide are suppressed; La 3+ It will also preferentially replace Ba in BaTiO3 2+ , Mg is introduced at the B position 2+ and Zr 4+ It can stably make up for the charge deficiency caused by this combination, and the high-valent Zr 4+ It can also compensate for oxygen vacancy defects; the substitution of other elements for Fe at the B position will form an iron-deficient state, thereby promoting Fe 3+ The formation of ions further reduces the concentration of oxygen vacancies. Under the synergistic effect of simultaneous doping at A and B sites, the concentration of oxygen vacancies inside the material is greatly reduced, effectively improving its disadvantage of large leakage current.

[0009] As the x value increases, the breakdown strength of the ceramic material is significantly improved from 60 kV / cm to 300 kV / cm. 3+ Mg 2+ and Zr4+ The introduction of ions also disrupts the originally long-range ordered ferroelectric domains in the ceramic material, forming short-range and disordered polar nanodomains, which enhances the relaxivity of the material. This is manifested in the original "fat" hysteresis loop gradually becoming thinner, the polarization difference increasing, and the energy storage efficiency being improved.

[0010] Preferably, the ceramic material further comprises 0.40-0.46wt% of MnO, 0.20-0.22wt% of Nd2O3, 0.10-0.17wt% of HfO2 and 0.10-0.15wt% of CaO, accounting for 0.40-0.46wt% of the base ceramic.

[0011] In the above technical solution, the addition of MnO inhibits the volatilization of bismuth during sintering, reduces the generation of voids, and improves the density of ceramics; the addition of Nd2O3: Nd 3+ It accumulates on the grain boundaries, grain growth is inhibited, and the grain size becomes smaller; HfO2 has a higher melting point, which is beneficial to improve the temperature stability of ceramics and realize their application in high-temperature environments; CaO can react with Fe2O3 below 1000°C to generate a low-melting-point compound Ca2Fe2O5, forming a trace liquid phase that acts as a mass transfer carrier during the sintering process, accelerating the migration of substances.

[0012] Another technical problem to be solved by the present invention is to provide a method for preparing the above-mentioned bismuth ferrite-based lead-free energy storage ceramic material, and the preparation method comprises the following steps:

[0013] (1) Weigh Bi2O3, Fe2O3, BaCO3, TiO2, La2O3, MgO, and ZrO2, and then pre-sinter to obtain (0.72-x)BiFeO3-0.28BaTiO3-xLa(Mg 1 / 2 Zr 1 / 2 )O3 based ceramic powder, wherein 0≤x≤0.24;

[0014] (2) mixing the basic ceramic powder obtained in step (1) with a solvent, a dispersant, a binder, and a plasticizer to obtain a casting slurry;

[0015] (3) casting the casting slurry obtained in step (2) into a membrane sheet, and pressing the obtained membrane sheet to obtain a ceramic green body;

[0016] (4) The ceramic green body obtained in step (3) is subjected to debinding and sintering to obtain the bismuth ferrite-based lead-free energy storage ceramic material.

[0017] Preferably, the purity of the compounds described in step (1) is greater than 98%, the ball milling time is 12 to 24 hours, the pre-sintering heating and cooling rates are 2 to 10°C / min, the sintering temperature is 600 to 800°C, and the temperature is kept at 2 to 3 hours.

[0018] Preferably, in step (2), the solvent comprises anhydrous ethanol accounting for 30-50 wt% of the casting slurry, the dispersant comprises tributyl phosphate accounting for 1-5 wt% of the casting slurry, the binder comprises polyvinyl butyral accounting for 5-10 wt% of the casting slurry, and the plasticizer comprises polyethylene glycol accounting for 0.5-3 wt% of the casting slurry.

[0019] Preferably, the pressing process in step (3) comprises:

[0020] Rolling: 20~30 passes;

[0021] Hot pressing: temperature 40~50℃, pressure 10~30 MPa, hold pressure for 20~30 minutes;

[0022] Cold isostatic pressing: pressure 100~200 MPa, hold pressure for 10~20 minutes.

[0023] Preferably, step (2) is: ball-milling 0.40-0.46wt% of MnO, 0.20-0.22wt% of Nd2O3, 0.10-0.17wt% of HfO2, and 0.10-0.15wt% of CaO, which account for 0.40-0.46wt% of the basic ceramic powder in step (1), with the basic ceramic powder to obtain a casting powder, and then mixing it with a solvent, a dispersant, a binder, and a plasticizer to obtain a casting slurry.

[0024] Preferably, the purity of the MnO, Nd2O3, HfO2 and CaO is greater than 98%, and the ball milling time is 12 to 24 h.

[0025] Specifically, in step (4), the debinding process can be as follows: heating to 500°C at 0.5°C / min, keeping the temperature for 300 minutes and then cooling naturally; the sintering process can be as follows: heating to 950°C at 2°C / min, keeping the temperature for 180 minutes and then cooling naturally.

[0026] Through the above technical solution, the present invention achieves the following beneficial effects:

[0027] 1. The present invention optimizes the material structure and designs a matrix ceramic having the following chemical formula: (0.72-x)BiFeO3-0.28BaTiO3-xLa(Mg 1 / 2 Zr 1 / 2 )O3, where 0≤x≤0.24. Compared with undoped BF-BT, the increase in x value significantly increases the breakdown field strength, and the hysteresis loop gradually becomes thinner, thereby improving the energy storage density and energy storage efficiency. The energy storage density and energy storage efficiency can be released at x=0.2 ( W rec =4.20 J / cm3 ) and x=0.24( η =86.3%). This design idea of ​​fundamentally improving structural defects by introducing ions has been verified in the present invention, opening up a new direction for the development of lead-free energy storage ceramic materials. At the same time, it also makes the material promising to become a new generation of environmentally friendly lead-free energy storage ceramic dielectric materials.

[0028] 2. In the preparation method of the present invention, the casting and rolling are combined, which effectively improves the density of the ceramic material and is beneficial to improving its energy storage performance; the process is simple and controllable, with high stability, the raw materials used are green and environmentally friendly, have no pollution to the environment, and have low overall cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 PE diagram of the bismuth ferrite-based lead-free energy storage ceramic material in an embodiment of the present invention, wherein (a) is not doped with MnO, Nd2O3, HfO2 and CaO, and (b) is doped with MnO, Nd2O3, HfO2 and CaO;

[0030] Figure 2 is the XPS graph of the bismuth ferrite-based lead-free energy storage ceramic material in Examples 7 and 11 of the present invention;

[0031] Figure 3 This is a density comparison chart of ceramics with different components;

[0032] Figure 4 are scanning electron microscope images, where (a) x = 0 without adding additives such as MnO, (b) x = 0 with adding additives such as MnO, (c) x = 0.2 without adding additives such as MnO, (b) x = 0.2 with adding additives such as MnO;

[0033] Figure 5 The electric domain structures of the ceramics in the embodiments of the present invention are as follows: (a) x=0, i.e., Embodiment 7; (b) x=0.2, i.e., Embodiment 11. DETAILED DESCRIPTION

[0034] The specific implementation of the present invention is described in detail below in conjunction with the examples. It should be understood that the specific implementation described herein is only used to illustrate and explain the present invention, and is not used to limit the present invention. For those of ordinary skill in the art, several modifications and improvements can be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0035] Embodiment 1:

[0036] A bismuth ferrite-based lead-free energy storage ceramic material, the ceramic material comprises a base ceramic having the following chemical formula: 0.72BiFeO3-0.28BaTiO3. The preparation method thereof is as follows:

[0037] (1) Weigh 60.6249g of 99% pure Bi2O3, 19.7375g of 99% Fe2O3, 19.4031g of 99% BaCO3 and 7.8939g of 98% TiO2, put them into a nylon jar with zirconium dioxide balls and anhydrous ethanol as ball milling media, and ball mill them in a ball mill for 12 hours. Then pre-sinter the mixed powder in a muffle furnace, the heating and cooling rate of the muffle furnace is 2℃ / min, the sintering temperature is 600℃, and the heat preservation is carried out for 2 hours to obtain the basic ceramic powder of 0.72BiFeO3-0.28BaTiO3.

[0038] (2) Mixing the obtained basic ceramic powder with anhydrous ethanol, tributyl phosphate, polyvinyl butyral, and polyethylene glycol to obtain a casting slurry, wherein anhydrous ethanol accounts for 30wt% of the basic ceramic powder, tributyl phosphate accounts for 2wt% of the basic ceramic powder, polyvinyl butyral accounts for 7wt% of the basic ceramic powder, and polyethylene glycol accounts for 3wt% of the basic ceramic powder.

[0039] (3) The obtained casting slurry is cast into a film sheet, and the size of a single casting film is 15 cm 15 cm, thickness 25 µm. 30 sheets of uniform film are selected and stacked in the stacking machine, and then sent to the finishing mill for 30 passes. The reduction in a single pass is controlled at 15% of the thickness before rolling. When the width exceeds 30%, the edge part is cut, and then the main part is divided and stacked. Repeat the operation, and the final rolling billet has a trimming size of 15 cm The rolled billet was hot pressed and cold isostatically pressed to obtain a ceramic green body. During the hot pressing process, the mold temperature was controlled at 40°C and the pressure was maintained at 10 MPa for 30 minutes. During the cold isostatic pressing process, the pressure was maintained at 100 MPa for 20 minutes.

[0040] (4) The obtained ceramic green body is subjected to debinding and sintering to obtain the bismuth ferrite-based lead-free energy storage ceramic material.

[0041] Embodiment 2:

[0042] A bismuth ferrite-based lead-free energy storage ceramic material, the ceramic material comprising a base ceramic having the following chemical formula: 0.66BiFeO3-0.28BaTiO3-0.06La(Mg 1 / 2 Zr 1 / 2 )O3. Its preparation method is as follows:

[0043] (1) Weigh 56.8942g of 99% pure Bi2O3, 18.4962g of 99% Fe2O3, 19.5258g of 99% BaCO3, 7.9525g of 98% TiO2, 3.4018g of 99.99% La2O3, 0.4126g of 99.9% MgO and 1.2976g of 99% ZrO2. Zirconium dioxide balls and anhydrous ethanol were used as ball milling media and loaded into a nylon jar with the raw materials, and ball milled in a ball mill for 14 hours. Then, the mixed powder was pre-sintered in a muffle furnace. The heating and cooling rate of the muffle furnace was 3℃ / min. The sintering temperature was 650℃ and kept warm for 2.5 hours to obtain 0.66BiFeO3-0.28BaTiO3-0.06La(Mg 1 / 2 Zr 1 / 2 )O3 based ceramic powder.

[0044] (2) The obtained basic ceramic powder is mixed with anhydrous ethanol, tributyl phosphate, polyvinyl butyral, and polyethylene glycol to obtain a casting slurry, wherein anhydrous ethanol accounts for 35wt% of the basic ceramic powder, tributyl phosphate accounts for 3wt% of the basic ceramic powder, polyvinyl butyral accounts for 8wt% of the basic ceramic powder, and polyethylene glycol accounts for 0.5wt% of the basic ceramic powder.

[0045] (3) The obtained casting slurry is cast into a film sheet, and the size of a single casting film is 15 cm 15 cm, thickness 25 µm. 30 sheets of uniform film are selected and stacked in the stacking machine, and then sent to the finishing mill for 20 passes. The reduction in a single pass is controlled at 15% of the thickness before rolling. When the width exceeds 30%, the edge part is cut, and then the main part is divided and stacked. Repeat the operation, and the final rolling billet has a trimming size of 15 cm The rolled billet was hot pressed and cold isostatically pressed to obtain a ceramic green body. During the hot pressing process, the mold temperature was controlled at 40°C and the pressure was maintained at 20 MPa for 25 minutes. During the cold isostatic pressing process, the pressure was maintained at 200 MPa for 10 minutes.

[0046] (4) The obtained ceramic green body is subjected to debinding and sintering to obtain the bismuth ferrite-based lead-free energy storage ceramic material.

[0047] Embodiment 3:

[0048] A bismuth ferrite-based lead-free energy storage ceramic material, the ceramic material comprising a base ceramic having the following chemical formula: 0.6BiFeO3-0.28BaTiO3-0.12La(Mg 1 / 2 Zr 1 / 2 )O3. Its preparation method is as follows:

[0049] (1) Weigh 52.6152g of 99% pure Bi2O3, 17.1423g of 99% Fe2O3, 19.6941g of 99% BaCO3, 8.0421g of 98% TiO2, 6.9213g of 99.99% La2O3, 0.8601g of 99.9% MgO and 2.6389g of 99% ZrO2. Zirconium dioxide balls and anhydrous ethanol were used as ball milling media and loaded into a nylon jar with the raw materials, and ball milled in a ball mill for 16 hours. Then, the mixed powder was pre-sintered in a muffle furnace. The heating and cooling rate of the muffle furnace was 4℃ / min. The sintering temperature was 700℃ and kept warm for 3 hours to obtain 0.6BiFeO3-0.28BaTiO3-0.12La(Mg 1 / 2 Zr 1 / 2 )O3 based ceramic powder.

[0050] (2) The obtained basic ceramic powder is mixed with anhydrous ethanol, tributyl phosphate, polyvinyl butyral, and polyethylene glycol to obtain a casting slurry, wherein anhydrous ethanol accounts for 40wt% of the basic ceramic powder, tributyl phosphate accounts for 4wt% of the basic ceramic powder, polyvinyl butyral accounts for 8wt% of the basic ceramic powder, and polyethylene glycol accounts for 1wt% of the basic ceramic powder.

[0051] (3) The obtained casting slurry is cast into a film sheet, and the size of a single casting film is 15 cm 15 cm, thickness 35 µm. Select 20 uniform membranes, stack them in the stacking machine, and send them to the finishing mill for 20 passes. The reduction in a single pass is controlled at 15% of the thickness before rolling. When the width exceeds 30%, the edge part is cut, and then the main part is divided and stacked. Repeat the operation, and the final rolling billet has a trimming size of 15 cm The rolled billet was hot pressed and cold isostatically pressed to obtain a ceramic green body. During the hot pressing process, the mold temperature was controlled at 45°C and the pressure was maintained at 20 MPa for 25 minutes. During the cold isostatic pressing process, the pressure was maintained at 150 MPa for 15 minutes.

[0052] (4) The obtained ceramic green body is subjected to debinding and sintering to obtain the bismuth ferrite-based lead-free energy storage ceramic material.

[0053] Embodiment 4:

[0054] A bismuth ferrite-based lead-free energy storage ceramic material, the ceramic material comprising a base ceramic having the following chemical formula: 0.54BiFeO3-0.28BaTiO3-0.18La(Mg 1 / 2 Zr 1 / 2 )O3. Its preparation method is as follows:

[0055] (1) Weigh 47.9649g of 99% pure Bi2O3, 15.6323g of 99% Fe2O3, 20.1819g of 99% BaCO3, 8.2733g of 98% TiO2, 10.4418g of 99.99% La2O3, 1.3188g of 99.9% MgO and 4.0102g of 99% ZrO2. Zirconium dioxide balls and anhydrous ethanol were used as ball milling media and loaded into a nylon jar with the raw materials, and ball milled in a ball mill for 18 hours. Then, the mixed powder was pre-sintered in a muffle furnace. The heating and cooling rate of the muffle furnace was 5℃ / min. The sintering temperature was 750℃ and kept warm for 2 hours to obtain 0.54BiFeO3-0.28BaTiO3-0.18La(Mg 1 / 2 Zr 1 / 2 )O3 based ceramic powder.

[0056] (2) Mixing the obtained basic ceramic powder with anhydrous ethanol, tributyl phosphate, polyvinyl butyral, and polyethylene glycol to obtain a casting slurry, wherein anhydrous ethanol accounts for 40wt% of the basic ceramic powder, tributyl phosphate accounts for 5wt% of the basic ceramic powder, polyvinyl butyral accounts for 9wt% of the basic ceramic powder, and polyethylene glycol accounts for 1.5wt% of the basic ceramic powder.

[0057] (3) The obtained casting slurry is cast into a film sheet, and the size of a single casting film is 15 cm 15 cm, thickness 35 µm. 30 sheets of uniform film are selected and stacked in the stacking machine, and then sent to the finishing mill for 30 passes. The reduction in a single pass is controlled at 15% of the thickness before rolling. When the width exceeds 30%, the edge part is cut, and then the main part is divided and stacked. Repeat the operation, and the final rolling billet has a trimming size of 15 cm The rolled billet was hot pressed and cold isostatically pressed to obtain a ceramic green body. During the hot pressing process, the mold temperature was controlled at 45°C and the pressure was maintained at 20 MPa for 30 minutes. During the cold isostatic pressing process, the pressure was maintained at 100 MPa for 10 minutes.

[0058] (4) The obtained ceramic green body is subjected to debinding and sintering to obtain the bismuth ferrite-based lead-free energy storage ceramic material.

[0059] Embodiment 5:

[0060] A bismuth ferrite-based lead-free energy storage ceramic material, the ceramic material comprising a base ceramic having the following chemical formula: 0.52BiFeO3-0.28BaTiO3-0.2La(Mg 1 / 2 Zr 1 / 2 )O3. Its preparation method is as follows:

[0061] (1) Weigh 46.3891g of 99% pure Bi2O3, 15.1412g of 99% Fe2O3, 20.1158g of 99% BaCO3, 8.2147g of 98% TiO2, 11.6315g of 99.99% La2O3, 1.4820g of 99.9% MgO and 4.4399g of 99% ZrO2. Zirconium dioxide balls and anhydrous ethanol were used as ball milling media and loaded into a nylon jar with the raw materials, and ball milled in a ball mill for 20 hours. Then, the mixed powder was pre-sintered in a muffle furnace. The heating and cooling rate of the muffle furnace was 6℃ / min. The sintering temperature was 800℃ and kept warm for 2.5 hours to obtain 0.52BiFeO3-0.28BaTiO3-0.2La(Mg 1 / 2 Zr 1 / 2 )O3 based ceramic powder.

[0062] (2) The obtained basic ceramic powder is mixed with anhydrous ethanol, tributyl phosphate, polyvinyl butyral, and polyethylene glycol to obtain a casting slurry, wherein anhydrous ethanol accounts for 45wt% of the basic ceramic powder, tributyl phosphate accounts for 4.5wt% of the basic ceramic powder, polyvinyl butyral accounts for 10wt% of the basic ceramic powder, and polyethylene glycol accounts for 3wt% of the basic ceramic powder.

[0063] (3) The obtained casting slurry is cast into a film sheet, and the size of a single casting film is 15 cm 15 cm, thickness 35 µm. 30 uniform membranes are selected and stacked in the stacking machine, and then sent to the finishing mill for 20 passes. The reduction in a single pass is controlled at 15% of the thickness before rolling. When the width exceeds 30%, the edge part is cut, and then the main part is divided and stacked. Repeat the operation, and the final rolling billet has a trimming size of 15 cm The rolled billet was hot pressed and cold isostatically pressed to obtain a ceramic green body. During the hot pressing process, the mold temperature was controlled at 50°C and the pressure was maintained at 10 MPa for 25 minutes. During the cold isostatic pressing process, the pressure was maintained at 100 MPa for 10 minutes.

[0064] (4) The obtained ceramic green body is subjected to debinding and sintering to obtain the bismuth ferrite-based lead-free energy storage ceramic material.

[0065] Embodiment 6:

[0066] A bismuth ferrite-based lead-free energy storage ceramic material, the ceramic material comprising a base ceramic having the following chemical formula: 0.48BiFeO3-0.28BaTiO3-0.24La(Mg 1 / 2 Zr 1 / 2 )O3. Its preparation method is as follows:

[0067] (1) Weigh 43.3195g of 99% pure Bi2O3, 14.1232g of 99% Fe2O3, 20.3620g of 99% BaCO3, 8.3332g of 98% TiO2, 14.1513g of 99.99% La2O3, 1.7352g of 99.9% MgO and 5.4283g of 99% ZrO2. Zirconium dioxide balls and anhydrous ethanol were used as ball milling media and loaded into a nylon jar with the raw materials, and ball milled in a ball mill for 24 hours. Then, the mixed powder was pre-sintered in a muffle furnace. The heating and cooling rate of the muffle furnace was 7℃ / min. The sintering temperature was 600℃ and kept warm for 3 hours to obtain 0.48BiFeO3-0.28BaTiO3-0.24La(Mg 1 / 2 Zr 1 / 2 )O3 based ceramic powder.

[0068] (2) The obtained basic ceramic powder is mixed with anhydrous ethanol, tributyl phosphate, polyvinyl butyral, and polyethylene glycol to obtain a casting slurry, wherein anhydrous ethanol accounts for 50wt% of the basic ceramic powder, tributyl phosphate accounts for 5wt% of the basic ceramic powder, polyvinyl butyral accounts for 5wt% of the basic ceramic powder, and polyethylene glycol accounts for 0.5wt% of the basic ceramic powder.

[0069] (3) The obtained casting slurry is cast into a film sheet, and the size of a single casting film is 15 cm 15 cm, thickness 30 µm. Select 25 uniform membranes, stack them in the stacking machine, and send them to the finishing mill for 25 passes. The reduction in a single pass is controlled at 15% of the thickness before rolling. When the width exceeds 30%, the edge part is cut, and then the main part is divided and stacked. Repeat the operation, and the final rolling billet has a trimming size of 15 cm The rolled billet was subjected to hot pressing and cold isostatic pressing to obtain a ceramic green body. During the hot pressing process, the mold temperature was controlled at 40°C and the pressure was maintained at 30 MPa for 30 minutes. During the cold isostatic pressing process, the pressure was maintained at 100 MPa for 20 minutes.

[0070] (4) The obtained ceramic green body is subjected to debinding and sintering to obtain the bismuth ferrite-based lead-free energy storage ceramic material.

[0071] Embodiment 7:

[0072] A bismuth ferrite-based lead-free energy storage ceramic material, the ceramic material comprises a base ceramic having the following chemical formula: 0.72BiFeO3-0.28BaTiO3. The preparation method thereof is as follows:

[0073] (1) Weigh 61.2373g of 99% pure Bi2O3, 19.9874g of 99% Fe2O3, 19.2110g of 99% BaCO3 and 7.8546g of 98% TiO2, put them into a nylon jar with zirconium dioxide balls and anhydrous ethanol as ball milling media, and ball mill them in a ball mill for 13 hours. Then pre-sinter the mixed powder in a muffle furnace, the heating and cooling rate of the muffle furnace is 8℃ / min, the sintering temperature is 650℃, and the temperature is kept for 2 hours to obtain 0.72BiFeO3-0.28BaTiO3 basic ceramic powder.

[0074] (2) Weigh 0.46wt% of MnO, 0.22wt% of Nd2O3, 0.10wt% of HfO2, and 0.10wt% of CaO in the base ceramic powder, mix them with the base ceramic powder by ball milling for 12 hours, and obtain a cast powder after sieving. Mix the obtained cast powder with anhydrous ethanol, tributyl phosphate, polyvinyl butyral, and polyethylene glycol to obtain a cast slurry. Among them, anhydrous ethanol accounts for 30wt% of the base ceramic powder, tributyl phosphate accounts for 2wt% of the base ceramic powder, polyvinyl butyral accounts for 6wt% of the base ceramic powder, and polyethylene glycol accounts for 1wt% of the base ceramic powder.

[0075] (3) The obtained casting slurry is cast into a film sheet, and the size of a single casting film is 15 cm 15 cm, thickness 25 µm. 30 sheets of uniform film are selected and stacked in the stacking machine, and then sent to the finishing mill for 20 passes. The reduction in a single pass is controlled at 15% of the thickness before rolling. When the width exceeds 30%, the edge part is cut, and then the main part is divided and stacked. Repeat the operation, and the final rolling billet has a trimming size of 15 cm The rolled billet was hot pressed and cold isostatically pressed to obtain a ceramic green body. During the hot pressing process, the mold temperature was controlled at 50°C and the pressure was maintained at 15 MPa for 30 minutes. During the cold isostatic pressing process, the pressure was maintained at 150 MPa for 15 minutes.

[0076] (4) The obtained ceramic green body is subjected to debinding and sintering to obtain the bismuth ferrite-based lead-free energy storage ceramic material.

[0077] Embodiment 8:

[0078] A bismuth ferrite-based lead-free energy storage ceramic material, the ceramic material comprising a base ceramic having the following chemical formula: 0.66BiFeO3-0.28BaTiO3-0.06La(Mg 1 / 2 Zr 1 / 2 )O3. Its preparation method is as follows:

[0079] (1) Weigh 56.9356g of 99% pure Bi2O3, 18.5833g of 99% Fe2O3, 19.4852g of 99% BaCO3, 7.8546g of 98% TiO2, 3.4127g of 99.99% La2O3, 0.4225g of 99.9% MgO and 1.3036g of 99% ZrO2, put them into a nylon jar with zirconium dioxide balls and anhydrous ethanol as ball milling media, and mill them in a ball mill for 15 hours. Then pre-sinter the mixed powder in a muffle furnace, the muffle furnace heating and cooling rate is 9℃ / min, the sintering temperature is 700℃, and the temperature is kept for 2.5 hours to obtain the basic ceramic powder.

[0080] (2) Weigh 0.40wt% of MnO, 0.20wt% of Nd2O3, 0.17wt% of HfO2, and 0.15wt% of CaO in the base ceramic powder, mix them with the base ceramic powder by ball milling for 14 hours, and obtain a cast powder after sieving. Mix the obtained cast powder with anhydrous ethanol, tributyl phosphate, polyvinyl butyral, and polyethylene glycol to obtain a cast slurry. Among them, anhydrous ethanol accounts for 40wt% of the base ceramic powder, tributyl phosphate accounts for 4wt% of the base ceramic powder, polyvinyl butyral accounts for 8wt% of the base ceramic powder, and polyethylene glycol accounts for 2.5wt% of the base ceramic powder.

[0081] (3) The obtained casting slurry is cast into a film sheet, and the size of a single casting film is 15 cm 15 cm, thickness 25 µm. 30 sheets of uniform film are selected and stacked in the stacking machine, and then sent to the finishing mill for 25 passes. The reduction in a single pass is controlled at 15% of the thickness before rolling. When the width exceeds 30%, the edge part is cut, and then the main part is divided and stacked. Repeat the operation, and the final rolling billet has a trimming size of 15 cm The rolled billet was hot pressed and cold isostatically pressed to obtain a ceramic green body. During the hot pressing process, the mold temperature was controlled at 40°C and the pressure was maintained at 20 MPa for 30 minutes. During the cold isostatic pressing process, the pressure was maintained at 200 MPa for 10 minutes.

[0082] (4) The obtained ceramic green body is subjected to debinding and sintering to obtain the bismuth ferrite-based lead-free energy storage ceramic material.

[0083] Embodiment 9:

[0084] A bismuth ferrite-based lead-free energy storage ceramic material, the ceramic material comprising a base ceramic having the following chemical formula: 0.6BiFeO3-0.28BaTiO3-0.12La(Mg 1 / 2 Zr 1 / 2 )O3. Its preparation method is as follows:

[0085] (1) Weigh 52.5093g of 99% pure Bi2O3, 17.1386g of 99% Fe2O3, 19.7674g of 99% BaCO3, 8.0822g of 98% TiO2, 6.9242g of 99.99% La2O3, 0.8572g of 99.9% MgO and 2.6450g of 99% ZrO2, put them into a nylon jar with zirconium dioxide balls and anhydrous ethanol as ball milling media, and ball mill them in a ball mill for 17 hours. Then, pre-sinter the mixed powder in a muffle furnace. The heating and cooling rate of the muffle furnace was 10℃ / min. The sintering temperature was 750℃. After keeping the temperature for 3 hours, 0.6BiFeO3-0.28BaTiO3-0.12La(Mg 1 / 2 Zr 1 / 2 )O3 based ceramic powder.

[0086] (2) Weigh 0.46wt% of MnO, 0.20wt% of Nd2O3, 0.17wt% of HfO2, and 0.10wt% of CaO in the base ceramic powder, mix them with the base ceramic powder by ball milling for 16 hours, and obtain a cast powder after sieving. Mix the obtained cast powder with anhydrous ethanol, tributyl phosphate, polyvinyl butyral, and polyethylene glycol to obtain a cast slurry. Among them, anhydrous ethanol accounts for 45wt% of the base ceramic powder, tributyl phosphate accounts for 1wt% of the base ceramic powder, polyvinyl butyral accounts for 10wt% of the base ceramic powder, and polyethylene glycol accounts for 3wt% of the base ceramic powder.

[0087] (3) The obtained casting slurry is cast into a film sheet, and the size of a single casting film is 15 cm 15 cm, thickness 25 µm. Select 20 uniform membranes and stack them in the stacking machine, and send them to the finishing mill for 20 passes. The reduction in each pass is controlled to be 15% of the thickness before rolling. When the width exceeds 30%, the edge part is cut, and then the main part is divided and stacked. Repeat the operation, and the final rolling billet has a trimming size of 15 cm The rolled billet was hot pressed and cold isostatically pressed to obtain a ceramic green body. During the hot pressing process, the mold temperature was controlled at 45°C and the pressure was maintained at 20 MPa for 30 minutes. During the cold isostatic pressing process, the pressure was maintained at 160 MPa for 10 minutes.

[0088] (4) The obtained ceramic green body is subjected to debinding and sintering to obtain the bismuth ferrite-based lead-free energy storage ceramic material.

[0089] Embodiment 10:

[0090] A bismuth ferrite-based lead-free energy storage ceramic material, the ceramic material comprising a base ceramic having the following chemical formula: 0.54BiFeO3-0.28BaTiO3-0.18La(Mg1 / 2 Zr 1 / 2 )O3. Its preparation method is as follows:

[0091] (1) Weigh 47.9529g of 99% pure Bi2O3, 15.6514g of 99% Fe2O3, 20.0580g of 99% BaCO3, 8.2010g of 98% TiO2, 10.5390g of 99.99% La2O3, 1.3048g of 99.9% MgO and 4.0257g of 99% ZrO2, put them into a nylon jar with zirconium dioxide balls and anhydrous ethanol as ball milling media, and ball mill them in a ball mill for 19 hours. Then, pre-sinter the mixed powder in a muffle furnace. The heating and cooling rate of the muffle furnace is 3℃ / min. The sintering temperature is 800℃. After keeping the temperature for 2 hours, 0.54BiFeO3-0.28BaTiO3-0.18La(Mg 1 / 2 Zr 1 / 2 )O3 based ceramic powder.

[0092] (2) Weigh 0.42wt% of MnO, 0.21wt% of Nd2O3, 0.13wt% of HfO2, and 0.12wt% of CaO in the base ceramic powder, mix them with the base ceramic powder by ball milling for 18 hours, and obtain a cast powder after sieving. Mix the obtained cast powder with anhydrous ethanol, tributyl phosphate, polyvinyl butyral, and polyethylene glycol to obtain a cast slurry. Among them, anhydrous ethanol accounts for 30wt% of the base ceramic powder, tributyl phosphate accounts for 2wt% of the base ceramic powder, polyvinyl butyral accounts for 8wt% of the base ceramic powder, and polyethylene glycol accounts for 3wt% of the base ceramic powder.

[0093] (3) The obtained casting slurry is cast into a film sheet, and the size of a single casting film is 15 cm 15 cm, thickness 25 µm. Select 20 uniform membranes and stack them in the stacking machine, and send them to the finishing mill for 30 passes. The reduction in a single pass is controlled at 15% of the thickness before rolling. When the width exceeds 30%, the edge part is cut, and then the main part is divided and stacked. Repeat the operation, and the final rolling billet has a trimming size of 15 cm The rolled billet was hot pressed and cold isostatically pressed to obtain a ceramic green body. During the hot pressing process, the mold temperature was controlled at 40°C and the pressure was maintained at 30 MPa for 20 minutes. During the cold isostatic pressing process, the pressure was maintained at 180 MPa for 8 minutes.

[0094] (4) The obtained ceramic green body is subjected to debinding and sintering to obtain the bismuth ferrite-based lead-free energy storage ceramic material.

[0095] Embodiment 11:

[0096] A bismuth ferrite-based lead-free energy storage ceramic material, the ceramic material comprising a base ceramic having the following chemical formula: 0.52BiFeO3-0.28BaTiO3-0.2La(Mg 1 / 2 Zr 1 / 2 )O3. Its preparation method is as follows:

[0097] (1) Weigh 46.4042g of 99% pure Bi2O3, 15.1460g of 99% Fe2O3, 20.1566g of 99% BaCO3, 8.2413g of 98% TiO2, 11.7676g of 99.99% La2O3, 1.4569g of 99.9% MgO and 4.4949g of 99% ZrO2, put them into a nylon jar with zirconium dioxide balls and anhydrous ethanol as ball milling media, and ball mill them in a ball mill for 21 hours. Then, pre-sinter the mixed powder in a muffle furnace. The heating and cooling rate of the muffle furnace is 5℃ / min. The sintering temperature is 600℃. After keeping the temperature for 2.5 hours, 0.52BiFeO3-0.28BaTiO3-0.2La(Mg 1 / 2 Zr 1 / 2 )O3 based ceramic powder.

[0098] (2) Weigh 0.44wt% of MnO, 0.22wt% of Nd2O3, 0.15wt% of HfO2, and 0.14wt% of CaO, and mix them with the basic ceramic powder by ball milling for 20 hours. After sieving, obtain a cast powder. Mix the obtained cast powder with anhydrous ethanol, tributyl phosphate, polyvinyl butyral, and polyethylene glycol to obtain a cast slurry. Among them, anhydrous ethanol accounts for 35wt% of the basic ceramic powder, tributyl phosphate accounts for 5wt% of the basic ceramic powder, polyvinyl butyral accounts for 8wt% of the basic ceramic powder, and polyethylene glycol accounts for 3wt% of the basic ceramic powder.

[0099] (3) The obtained casting slurry is cast into a film sheet, and the size of a single casting film is 15 cm 15 cm, thickness 25 µm. 30 sheets of uniform film are selected and stacked in the stacking machine, and then sent to the finishing mill for 20 passes. The reduction in a single pass is controlled at 15% of the thickness before rolling. When the width exceeds 30%, the edge part is cut, and then the main part is divided and stacked. Repeat the operation, and the final rolling billet has a trimming size of 15 cm The rolled billet was hot pressed and cold isostatically pressed to obtain a ceramic green body. During the hot pressing process, the mold temperature was controlled at 45°C and the pressure was maintained at 20 MPa for 30 minutes. During the cold isostatic pressing process, the pressure was maintained at 100 MPa for 10 minutes.

[0100] (4) The obtained ceramic green body is subjected to debinding and sintering to obtain the bismuth ferrite-based lead-free energy storage ceramic material.

[0101] Embodiment 12:

[0102] A bismuth ferrite-based lead-free energy storage ceramic material, the ceramic material comprising a base ceramic having the following chemical formula: 0.48BiFeO3-0.28BaTiO3-0.24La(Mg 1 / 2 Zr 1 / 2 )O3. Its preparation method is as follows:

[0103] (1) Weigh 43.2605g of 99% pure Bi2O3, 14.1199g of 99% Fe2O3, 20.3571g of 99% BaCO3, 8.3232g of 98% TiO2, 14.2616g of 99.99% La2O3, 1.7656g of 99.9% MgO and 5.4476g of 99% ZrO2, put them into a nylon jar with zirconium dioxide balls and anhydrous ethanol as ball milling media, and mill them in a ball mill for 23 hours. Then, pre-sinter the mixed powder in a muffle furnace. The heating and cooling rate of the muffle furnace is 7℃ / min. The sintering temperature is 700℃. After keeping warm for 3 hours, 0.48BiFeO3-0.28BaTiO3-0.24La(Mg 1 / 2 Zr 1 / 2 )O3 based ceramic powder.

[0104] (2) Weigh 0.45wt% of MnO, 0.20wt% of Nd2O3, 0.16wt% of HfO2, and 0.11wt% of CaO in the base ceramic powder, mix them with the base ceramic powder by ball milling for 24 hours, and obtain a cast powder after sieving. Mix the obtained cast powder with anhydrous ethanol, tributyl phosphate, polyvinyl butyral, and polyethylene glycol to obtain a cast slurry. Among them, anhydrous ethanol accounts for 40wt% of the base ceramic powder, tributyl phosphate accounts for 3wt% of the base ceramic powder, polyvinyl butyral accounts for 9wt% of the base ceramic powder, and polyethylene glycol accounts for 2.5wt% of the base ceramic powder.

[0105] (3) The obtained casting slurry is cast into a film sheet, and the size of a single casting film is 15 cm 15 cm, thickness 30 µm. Select 20 uniform membranes, stack them in the stacking machine, and send them to the finishing mill for 25 passes. The reduction in a single pass is controlled at 15% of the thickness before rolling. When the width exceeds 30%, the edge part is cut, and then the main part is divided and stacked. Repeat the operation, and the final rolling billet has a trimming size of 15 cm The rolled billet was hot pressed and cold isostatically pressed to obtain a ceramic green body. During the hot pressing process, the mold temperature was controlled at 48°C and the pressure was maintained at 20 MPa for 25 minutes. During the cold isostatic pressing process, the pressure was maintained at 140 MPa for 14 minutes.

[0106] (4) The obtained ceramic green body is subjected to debinding and sintering to obtain the bismuth ferrite-based lead-free energy storage ceramic material.

[0107] Reference Figure 1 As the x content increases, the breakdown strength of the ceramic is improved, and the hysteresis loop gradually becomes thinner. Finally, the energy storage performance of the bismuth ferrite-based lead-free energy storage ceramic material is greatly improved. When x=0.2, it reaches 4.2 J / cm at an electric field strength of 280 kV / cm. 3 The releasable energy storage density and energy storage efficiency of 75.2% are achieved.

[0108] By comparing the PE diagrams with and without the addition of additives such as MnO, it can be proved that the addition of MnO, Nd2O3, HfO2 and CaO effectively improves the energy storage performance of ceramics.

[0109] Reference Figure 2 , (a) and (b) in the figure are the distribution of oxygen content in the bismuth ferrite-based lead-free energy storage ceramic material when x=0 and x=0.2 respectively. It can be clearly seen that before the introduction of the new component (i.e. x=0), the oxygen vacancy concentration in the material is higher than the lattice oxygen concentration, and the calculated oxygen vacancy content is 56.7%. Through the effect of doping ions (i.e. x=0.2), the concentration of oxygen vacancies is significantly reduced to 37.15%, a decrease of more than 1 / 3 of the original value.

[0110] Reference Figure 3 With the increase of x content, the density of ceramics increases significantly; the density of ceramics with MnO and other additives is better than that of ceramics without additions.

[0111] Reference Figure 4 The ceramic grain size with the addition of MnO and the like is more uniform and the density is better, which is conducive to obtaining higher breakdown strength.

[0112] Reference Figure 5 As the x content increases, the electric domain changes from a long-range ferroelectric domain when x = 0 to a nano-domain when x = 0.2. The reduction of the electric domain is conducive to achieving a faster electrical response, thereby reducing losses and improving energy storage efficiency.

[0113] The preferred implementation modes of the present invention are described in detail above in combination with the embodiments; however, the present invention is not limited to the specific details in the above implementation modes. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical scheme of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0114] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0115] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A method for preparing a bismuth ferrite-based lead-free energy storage ceramic material, characterized in that: The steps include: (1) Weigh Bi2O3, Fe2O3, BaCO3, TiO2, La2O3, MgO, and ZrO2, and then pre-sinter to obtain (0.72-x)BiFeO3-0.28BaTiO3-xLa(Mg 1 / 2 Zr 1 / 2 )O3 based ceramic powder, wherein 0.06≤x≤0.24; (2) ball-milling the basic ceramic powder of step (1) with 0.40-0.46 wt% of MnO, 0.20-0.22 wt% of Nd2O3, 0.10-0.17 wt% of HfO2, and 0.10-0.15 wt% of CaO, which account for 0.40-0.46 wt% of the basic ceramic powder, to obtain a tape-casting powder, and then mixing the powder with a solvent, a dispersant, a binder, and a plasticizer to obtain a tape-casting slurry; (3) casting the casting slurry obtained in step (2) into a membrane sheet, and pressing the obtained membrane sheet to obtain a ceramic green body; (4) The ceramic green body obtained in step (3) is subjected to debinding and sintering to obtain the bismuth ferrite-based lead-free energy storage ceramic material.

2. The preparation method according to claim 1, characterized in that: The value range of x is 0.06~0.

20.

3. The preparation method according to claim 2, characterized in that: The value range of x is 0.12~0.

18.

4. The preparation method according to claim 1, characterized in that: In step (1), the purity of Bi2O3, Fe2O3, BaCO3, TiO2, La2O3, MgO and ZrO2 is greater than 98%, the ball milling time is 12 to 24 hours, the pre-sintering heating and cooling rates are 2 to 10°C / min, the sintering temperature is 600 to 800°C, and the temperature is kept at 2 to 3 hours.

5. The preparation method according to claim 1, characterized in that: In step (2), the solvent comprises anhydrous ethanol accounting for 30-50 wt% of the base ceramic powder, the dispersant comprises tributyl phosphate accounting for 1-5 wt% of the base ceramic powder, the binder comprises polyvinyl butyral accounting for 5-10 wt% of the base ceramic powder, and the plasticizer comprises polyethylene glycol accounting for 0.5-3 wt% of the base ceramic powder.

6. The preparation method according to claim 1, characterized in that: The pressing process in step (3) includes: Rolling: 20~30 passes; Hot pressing: temperature 40~50℃, pressure 10~30MPa, hold pressure for 20~30 minutes; Cold isostatic pressing: pressure 100~200 MPa, hold pressure for 10~20 minutes.

7. The preparation method according to claim 1, characterized in that: The purities of the MnO, Nd2O3, HfO2 and CaO are all greater than 98%, and the ball milling time is 12 to 24 hours.

Citation Information

Patent Citations

  • Bismuth ferrite-barium titanate based high-temperature lead-free piezoelectric ceramic with low dielectric loss and high-temperature stability and preparation method thereof

    CN110272270A

  • Lead-free bismuth ferrite-based ceramic material and preparation method thereof

    CN111205082A

  • Preparation method of doped bismuth ferrite-barium titanate leadless piezoelectric ceramic material

    CN111320468A

  • Doped modified bismuth ferrite-based lead-free energy storage material and preparation method thereof

    CN115572161A

  • High-entropy perovskite oxide doped ceramic, preparation method and application thereof

    CN115991599A